GEOMORPHOLOGY CHARACTERISTIC OF CIANGSANA AND SURROUNDING AREAS, CIKEMBAR SUB-DISTRICT, SUKABUMI REGENCY, WEST JAVA - Cahyadi, Hary (Departemen Teknik Geologi, 2016)
Geomorphology as a branch of geology that has a very important role to give an overview and information on the existing landscape in an area. One of the interesting areas for further investigation geomorphology characteristics is Ciangsana. Ciangsana administratively included in Cikembar subdistricts bordering Cibadak sub-district, Sukabumi Regency, West Java. The purpose of this paper is to map the geomorphology characteristics of the research area that can provide information to the communities living nearby in order to become the reference in infrastructure development activities and disaster mitigation. The method used is the analysis of geomorphology that includes morphometry (slope), morphograpy (absolute altitude), morphogenetic (genetic class) and river flow patterns. Based on the analysis will be produced geomorphology unit. It can be concluded that the research area can be divided into three geomorphological units, namely: steep volcanic hills, gentle volcanic hills, and steep sedimentary hills. Kata kunci : Ciangsana, Geomorphoology, Morphometry, Morphografy, Morphogenetic